Faith, film and philosophy big ideas on the big screen - Geivett, R. Douglas; Spiegel, James S., 1963- (Downers Grove, Ill. : IVP Academic, 2007)
Fourteen essays consider classic and current films together with several major philosophical themes, all within the context of Christian faith: (1) the human condition, (2) the human mind and the nature of knowing, (3) the moral life, and (4) faith and religion.
Part 1. The human condition -- The Citizen Kane Mutiny : what Hollywood knows and will never admit about life, love, and human relationships / James F. Sennett -- Story-shaped lives in Big Fish / Kelly J. Clark -- Defining love through the eye of the lens : romance, sex, and the human condition in Pretty Woman, Legends of the Fall and The Bridges of Madison County / Greg Jesson -- Part 2. Mind and knowledge -- Escaping into reality : What we can learn from The Truman Show about the knowledge enterprise / R. Douglas Geivett -- The sleeper awakes : Gnosis and authenticity in The Matrix / David P. Hunt -- Consciousness, memory, and identity : the nature of persons in three films by Charlie Kaufman / Gregory E. Ganssle -- What would have been and what could be : counterfactuals in It's a Wonderful Life and Run Lola Run / James S. Spiegel -- Part 3. The moral life -- Liberation through sensuality : cinematic moral vision in an age of feeling / Dallas Willard -- From a society of fear to a community of trust : moving beyond Bowling for Columbine / Sara L. H. Shady -- Vengeance, forgiveness and redemption in Mystic River / Caroline J. Simon -- Moral monsters : horror's indispensable need for good and evil -- Part 4. Faith and religion -- Religion and science in Contact and 2001: a Space Odyssey / Brendan Sweetman -- Bottled water from the fragrant harbor : the diluted spiritual elements of Hong Kong films / Winfried Corduan -- Rattle and film : U2, Niezsche and salvation in the blues / Douglas K. Blount.
Includes bibliographical references (p. [283]-302) and index.
Description based on print version record.
Keywords: Motion pictures -- Moral and ethical aspects; Motion pictures -- Religious aspects; Film -- Motiv -- Religion; Religion -- Motiv -- Film; Film -- Philosophie; Philosophie -- Film; Ethik; Religion; Moral; Film; Philosophie; Film; Christentum; Philosophie; USA; PERFORMING ARTS / Reference; Electronic books